1983
DOI: 10.2527/jas1983.5751182x
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Energy Intake and Elevated Calcium and Phosphorus Intake for Boars during Growth. II. Foot and Leg Measurements and Toe and Soundness Scores

Abstract: Boars were assigned at 5 wk of age in a 2 X 2 factorial arrangement to two energy (ad libitum and 75% of ad libitum) and two Ca and P levels (100 and 150% of the National Research Council daily recommended amounts) to determine the effect of reduced growth rate and elevated Ca and P intake on foot and leg measurements, pad and horn incidence and severity of lesions, and structural soundness. There were 20 boars/treatment; 15 boars from each treatment were necropsied at 10 +/- 2-d intervals from 80 to 220 d of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
3
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…In agreement, Vaughan (1971) suggested that rapid growth may predispose an animal to leg weakness problems. In contrast, Kornegay et al (1983) reported that ad libitum-fed boars showed increased soundness score when the scores were cor- The present study supports the results of Nimmo et al (1980a,b), Kornegay et al (1981Kornegay et al ( , 1983 and Calabotta et al (1982) (Calabotta 1979;Bryant 1982) and with sows (Bryant 1982;Arthur et al 1983) (Braude and Townsend 1958;Frape et al 1959;Nielsen 1964;'Calabotta et al 1982;Kesel et al 1983). …”
supporting
confidence: 88%
See 2 more Smart Citations
“…In agreement, Vaughan (1971) suggested that rapid growth may predispose an animal to leg weakness problems. In contrast, Kornegay et al (1983) reported that ad libitum-fed boars showed increased soundness score when the scores were cor- The present study supports the results of Nimmo et al (1980a,b), Kornegay et al (1981Kornegay et al ( , 1983 and Calabotta et al (1982) (Calabotta 1979;Bryant 1982) and with sows (Bryant 1982;Arthur et al 1983) (Braude and Townsend 1958;Frape et al 1959;Nielsen 1964;'Calabotta et al 1982;Kesel et al 1983). …”
supporting
confidence: 88%
“…In contrast, several other researchers have reported no beneficial effect of energy restriction (Fell et al l97O;Nakano et al 1979;Calabotta etal. 1982;Kornegay et al 1983;Arthur et al 1983). Likewise, feeding Ca and P levels in excess of National Academy of Sciences-National Research Council (NAS-NRC 1979) recommendations have not improved structural soundness scores in gilts (Calabotta et al 1982) and boars (Nimmo et al l980a,b;Kornegay et al 1981Kornegay et al , 1983).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In another paper in this series, Lepine et al (1985) found that elevating mineral and vitamin intake above that recommended by NAS-NRC (1979) had no effect on toe, foot and leg development and resulting structural soundness, which agrees with previous reports (Grondalen 1976;Reiland 1978;Nimmo et al 1980b;Kornegay and Thomas 1981;Kornegay et al 1981Kornegay et al , 1983Calabotta etal. 1982;Arther et al 1983a …”
supporting
confidence: 82%
“…Some authors suggested that pigs excelling in growth rate encounter a greater degree of leg weakness problems than slower growing counterparts (Grondalen, 1974;Lundeheim, 1987). In contrast, other studies reported reduced leg weakness with faster growth (Reiland et al, 1978;Kornegay et al, 1983) or no apparent relationship between the two traits (Kornegay et al, 1981;Webb et al, 1983;Rothschild et al, 1988). Correspondingly, increased incidence of osteochondrosis was associated with rapid growth rate in an earlier study of Goedegebuure et al (1980).…”
Section: An Initial Study Bymentioning
confidence: 86%